Інформаційне забезпечення діяльності наукових установ в мережі Інтернет - Сєров, Юрій; Приставська, Марія (Видавництво Львівської політехніки, 2012)
The article is considered legislative base of informatization of Ukrainian research institutions. Typical structure of web-sites is putted forward and choice of software base for web-site’s creation is given.
Keywords: інформатизація; наукова установа; Інтернет; інформаційне забезпечення; програмна база